2014
DOI: 10.3233/jad-132720
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Therapeutic Action of Retinoic Acid Receptor and Retinoid X Receptor Agonists in a Mouse Model of Alzheimer's Disease

Abstract: Abstract. Alzheimer's disease (AD) is a neurodegenerative process involving amyloid-␤ (A␤) peptide deposition, neuroinflammation, and progressive memory loss. Here, we evaluated whether oral administration of retinoic acid receptor (RAR)␣,␤ agonist Am80 (tamibarotene) or specific retinoid X receptor (RXR) pan agonist HX630 or their combination could improve deficits in an AD model, 8.5-month-old amyloid-␤ protein precursor 23 (A␤PP23) mice. Co-administration of Am80 (0.5 mg/kg) and HX630 (5 mg/kg) for 17 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 77 publications
0
25
1
Order By: Relevance
“…In addition, a positive correlation was observed between RARβ and IDE in the current study. This result supports a recent study reporting that RARα and RARβ agonists enhanced the expression of IDE [20]. Moreover, we found that RARα and RARγ were negatively correlated with IDE, which is inconsistent with a previous in vitro study showing that RA-elicited RARα induced IDE expression [46].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In addition, a positive correlation was observed between RARβ and IDE in the current study. This result supports a recent study reporting that RARα and RARβ agonists enhanced the expression of IDE [20]. Moreover, we found that RARα and RARγ were negatively correlated with IDE, which is inconsistent with a previous in vitro study showing that RA-elicited RARα induced IDE expression [46].…”
Section: Discussioncontrasting
confidence: 63%
“…ADAM10, the central component of α-secretase, was identified as a key molecule in RA-mediated anti-AD mechanisms [45]. In addition, RA can increase Aβ clearance by enhancing the expression of the Aβ-degrading enzyme IDE [20, 46]. Moreover, the IDE gene contains a RARE in its promoter region [41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the short time, RA can repair DSBs and appears even to increase viability in the cortex of young and to a lesser extent of aged mice. The fact that RA is repairing DSBs as Am80 and trichostatin A and that both of them alter memorization [ 49 , 50 ] suggests a similar role for RA. We make the hypothesis that whereas A β produces DSBs, RA results in targeted error-prone repair of the subset of DNA regions with RA-dependent gene expression, involved in particular in neuronal or synaptic maintenance [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been implicated in the control of rhythms within the brain (Ransom et al, 2014). In addition, alterations in the expression of some of the components of RA signaling may contribute to the pathophysiology of various neurodegenerative diseases including ALS (Jokic et al, 2007; Kolarcik and Bowser, 2012) and Alzheimer's disease (Corcoran et al, 2004; Kawahara et al, 2014). …”
Section: Introductionmentioning
confidence: 99%